Growing into democracy, justification and autonomy for youth in Denmark and Sweden - Sjöstedt, William (Politica, 2021)
Is it legitimate to exclude youth from Denmark and Sweden’s democracies? This article starts from the ideal that democracy and personal autonomy are deeply connected, in theory and in the context. A policy analysis is conducted on youth participation and autonomy from a critical perspective of democracy as justification of a social order. The aim is to clarify the normative background of youth exclusion contextually and evaluate its legitimacy. The analysis shows that the primary purpose of inclusion is development of capacity for autonomy and that the right to ethical autonomy is respected unless it threatens development of future autonomy. However, a wide set of legal and social responsibilities placed on young people have no corresponding democratic rights, motivated by a lack of capacity for autonomy. This is a form of arbitrary rule, and youth are justified to demand more access to democratic participation. Keywords: democratic legitimacy, critical theory, youth, Denmark, Sweden